2012
DOI: 10.1029/2012jc008263
|View full text |Cite
|
Sign up to set email alerts
|

The age of Yellow River water in the Bohai Sea

Abstract: To quantitatively understand the transport timescales of dissolved material discharged from large rivers into a semienclosed sea, the age of Yellow River water in the Bohai Sea was calculated with the constituent‐oriented age and residence time theory (CART) and particle‐tracking method. Yellow River water has a mean age of 3.0 years for the entire Bohai Sea. The spatial variation of the water age is significant: 1.2 years near the Yellow River estuary but 3.9 years in the Liaodong Bay. However, the temporal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Fig. 8b), being typically~0.02e0.03 m s À1 in calm weather and <0.1 m s À1 during storms, in agreement with the observations of Liu et al (2012) and Wang et al (2014).…”
Section: Predictionssupporting
confidence: 84%
See 2 more Smart Citations
“…Fig. 8b), being typically~0.02e0.03 m s À1 in calm weather and <0.1 m s À1 during storms, in agreement with the observations of Liu et al (2012) and Wang et al (2014).…”
Section: Predictionssupporting
confidence: 84%
“…From these modeling studies, it was suggested that Yellow Sea waters enter Bohai Strait in the north while Bohai Sea water flows out to the Yellow Sea through the strait in the south (Huang et al, 1999;Fang et al, 2000;Cheng et al, 2004;Hainbucher et al, 2004;Li et al, 2005;Lu et al, 2011;Liu et al, 2012). These models were also used to estimate the residence time in the Bohai Sea.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Their spreading and deposition control the biological and sedimentological dynamics, and hence, the ecological and morphological state of the Bohai Sea. To quantitatively understand the transport timescales of dissolved material discharged from large rivers into a semi-enclosed sea, the age of Yellow River water in the Bohai Sea was calculated using numerical models ( Liu et al, 2012) . The results showed that the Yellow River water has a mean age of 3. 0 years for the entire Bohai Sea, with a range of 1. 2~3. 9 years increasing from the Yellow River estuary towards the Liaodong Bay.…”
Section: Transport Processesmentioning
confidence: 99%
“…Water age, which is defined as ''the time that has elapsed since the particle under consideration left the region in which its age is prescribed as being zero" (Delhez et al, 1999), is a useful indicator for the temporal and spatial quantification of the transport time of pollutants (Takeoka, 1984;Boynton et al, 1995;Delhez et al, 1999;Shen and Wang, 2007;Li et al, 2011). The concept of water age has been extensively applied in coastal water areas with intense water exchange, which is induced by tides and wind (Deleersnijder et al, 2001;Liu and Huang, 2009;Liu et al, 2012), and lakes and reservoirs with intense water movement, which is induced by human regulations Shen et al, 2011;Wu et al, 2013). These studies also explored the dominant controlling factors of water age, such as the inflow/outflow and wind.…”
Section: Introductionmentioning
confidence: 99%